Medical costs of Japanese lung cancer patients during end-of-life care. (28th January 2021) - Awano, Nobuyasu; Izumo, Takehiro; Inomata, Minoru; Kuse, Naoyuki; Tone, Mari; Takada, Kohei; Muto, Yutaka; Fujimoto, Kazushi; Kimura, Hitomi; Miyamoto, Shingo; Igarashi, Ataru; Kunitoh, Hideo
Abstract: Objective: The medical costs associated with cancer treatment have increased rapidly in Japan; however, little data exist on actual costs, especially for end-of-life care. Therefore, this study aimed to examine the medical costs of lung cancer patients during the last 3 months before death and to compare the costs with those of initial anticancer treatment. Methods: We retrospectively evaluated all patients who died from lung cancer at the Japanese Red Cross Medical Center between 1 January 2008 and 31 August 2019. Patients were classified into three cohorts (2008–2011, 2012–2015 and 2016–2019) according to the year of death; the medical costs were evaluated for each cohort. Costs were then divided into outpatient and inpatient costs and calculated per month. Results: Seventy-nine small cell lung cancer and 213 non-small cell lung cancer patients were included. For small cell lung cancer and non-small cell lung cancer patients, most end-of-life medical costs were inpatient costs across all cohorts. The median monthly medical costs for the last 3 months among both small cell lung cancer and non-small cell lung cancer patients did not differ significantly among the cohorts, but the mean monthly costs for non-small cell lung cancer tended to increase. The monthly medical costs for the last 3 months were significantly higher than those for the first year in SCLC ( P  = 0.013) and non-small cell lung cancer ( P  < 0.001) patients and those for the first 3 months in non-small cell lung cancer patients ( P  = 0.005). Conclusions: The medical costs during the end-of-life period for lung cancer were high and surpassed those for initial treatment. Abstract : The medical costs for end-of-life care for lung cancer were high and were higher than the initial treatment costs.